Characterizing the Dependence on Non-timber Forest Products Among Communities Living Around Forest Conservation Areas in Marrupa-Mecula Corridor, Niassa Special Reserve, Niassa Province of Mozambique - Lubega, Gerald; Falcão, Mário Paulo; Ssekandi, Joseph; Ribeiro, Natasha Sofia (Frontiers in Forests and Global Change, 2022)
The role of forests across the world has been recognized as key natural assets that offer several goods and services, especially to communities adjacent to them. Given this role, there have been minimal efforts to determine the factors characterizing this dependence of communities on non-timber forest products (NTFPs), especially in developing nations. This study surveyed and assessed different factors influencing household dependence on NTFPs in the Marrupa-Mecula Corridor, Niassa Special Reserve, Niassa Province of Mozambique. In total, 377 household members from eight villages attended the interview while employing proportional random sampling. Data analysis was done using descriptive statistics and binary logistic regression. The study revealed that 90.9% of the households participate in collecting, producing, and selling NTFPs. Three factors, namely, social, economic, and physical, with twenty sub-factors or characteristics were found to have a significant association with dependence on forest resources. They include the availability of NTFPs, taking a collection of NTFPs as a family job, strong cultural attachment to forests, seasonal engagement in collection, nearby forests being home for community leaders, distance to the nearby forest, the housing needs of forests, forests being a major source of medicine, forests being a resource for educational institutions, forests being a major source of household food security, forests being a ready income for households, forests being a tourist attraction in the area, and affordability of distance to markets. The binary logistic regression revealed that gender, age, education, family size, and time spent in the area are significantly associated with dependence on NTFPs. Additionally, strong cultural attachment to forests, seasonal engagement in collection, nearby forests being homes for community leaders, distance to the nearby forest, housing needs, a major source of medicine, education, household food security, ready income, tourist attraction, and affordability of distance to markets were found to have a significant influence. On the contrary, scary dangerous wild animals, restriction of cultivation in non-gazetted forests, restriction of hunting in non-gazetted forests, and forest fires negatively affected the dependence on NTFPs/resources. As a way of achieving sustainable utilization of NTFPs, management plans and strategies need to incorporate these factors characterizing the dependence on NTFPs.